Relationships among ICT, ageing, and health expenditures in Japan: An economic evaluation - Sheikh Abu Taher; Kamal Uddin; Masatsugu Tsuji (International Telecommunications Society (ITS), 2017)
The paper examines the relationship among Information and Communication Technology (ICT), ageing, and health expenditures in Japan. For this, primary data has been collected from an extensive mail survey that was carried in Nishiaizu Town, Fukushima prefecture, Japan from 2002 to 2010. 9 years panel data is used to empirically identify the determinants of health expenditure in relation to ageing and telehealth use. Also, the effects are analyzed by comparison of medical expenditures between users and non-users of telehealth. Their receipts from those stored in the town office are examined too. The receipts of National Health Insurance of each month are kept at the town office. The paper uses mainly the following data, as: (i) name of resident, (ii) date of birth, (iii) either regular outpatient treatment or hospitalized patient treatment, (iv) name(s) of major disease(s), (v) date of initial treatment, (vi) number of days spent for treatment, and (vii) score (amount) of medical expenditure. Besides, other variables such as the availability of chronic disease among the participants, types of chronic diseases such as heart disease, high blood pressure, diabetes, and strokes, living alone or with family and employment status have also considered for the analysis. Using these variables, a rigorous econometric model is estimated. The estimation model is panel data analysis with the one-way fixed effect model with only time effect. A user dummy variable is added as an explanatory variable, which enables to estimate whether there is difference between users and non-users in medical expenditures of each disease of ageing. Based on the data obtained, the objectives of the estimation consists of the following three questions: (i) whether there is difference in medical expenditures among users and non-users of telehealth use; and (ii) how medical expenditures related to chronic diseases were different among two groups, user and non-user. (iii) how the use of telehealth can reduce medical expenditures of ageing.
Keywords: 330; health expenditure; economic evaluation; panel data; Japan; telemedicine